Determinant Factors of Behavior of Women of Reproductive Age on Early Detection of Cervic Cancer - Agustina, Weni; Prihatin Era, Dwi; Ersya Urnia, Ega (Jurnal KESANS : Kesehatan dan Sains, 2023)
Introduction: Cervical cancer is the second most common problem in Indonesia with the main cause of death for women globally. Cervical cancer itself can be detected using the IVA examination method in women of reproductive age. Objective: Identify the determinants of the behavior of women of reproductive age towards screening for early detection of cervical cancer in Muara Kaman Ulu Village in 2023. Method: This research is a quantitative survey method with a cross-sectional approach. The population in this study were women of reproductive age who met the inclusion criteria. The sample used was 85 respondents with purposive sampling technique. Results and Discussion: The results of the analysis showed that there was a significant relationship between age, attitude, knowledge, family support, and socio-culture on the behavior of early detection of cervical cancer with a p value < ? (0.05). Age, attitude, knowledge, family support and socio-culture are factors related to the behavior of women of childbearing age to carry out screening for early detection of cervical cancer. Conclusion: There is a relationship between age, attitude, knowledge, family support and socio-culture towards the behavior of women of reproductive age towards early detection of cervical cancer in Muara Kaman Ulu Village in 2023.